KEWIRAUSAHAAN DAN PERTUMBUHAN EKONOMI INDONESIA: DYNAMIC STOCHASTIC MODELLING - Samuel Dendy Krisandi; Hasymi Rinaldi; Mahendra Jaya; Ade M. Yuardani (Yayasan Nusantara Hasana Berdikari, 2023)
Uncertainty economic inflation has been dispersed to all countries whether developed countries or emerging countries. Indonesia as an emerging country is affected as well in economic growth decrement. This study aims to find a model of dynamic stochastic using Bayesian analysis of Monte Carlo and forth prediction of Indonesia economic performance. The concordance data of this study has been collected from World Bank, OECD in 1961 to 2020. Entrepreneurship Policy (EP), Gross Domestic Product (GDP), Foreign Direct Investment (FDI), Total Factor Productivity (TFP), Exchange Rate (RER), Household Consumption (HC), Inflation (INF) are being used at achieving equilibrium model by dynamic stochastic modelling analysis. The results revealed that inflation effect on Indonesia economic growth will be ahead until 2035 by no means that influences are performed through Entrepreneurship Policy (EP), Foreign Direct Investment (FDI), Exchange Rate (RER). Nevertheless, Indonesia demographic advantages lead to a higher demand of consumption. Indonesia still has a modest range of total factor productivity that need to be concerned for economic recovery.